Tityus serrulatus Scorpion Venom Induces Apoptosis in Cervical Cancer Cell Lines. (23rd June 2019) - Bernardes-Oliveira, Emanuelly; Farias, Kleber Juvenal Silva; Gomes, Dayanne Lopes; Araújo, Josélio Maria Galvão de; Silva, Wilmar Dias da; Rocha, Hugo Alexandre Oliveira; Donadi, Eduardo Antônio; Fernandes-Pedrosa, Matheus de Freitas; Crispim, Janaina Cristiana de Oliveira
Abstract : Cervical cancer (CC) is classified as the fourth most common type of cancer in women worldwide and remains a serious public health problem in many underdeveloped countries. Human papillomavirus (HPV), mainly types 16 and 18, has been established as a precursory etiologic agent for this type of cancer. Several therapeutic attempts have been studied and applied, aiming at its control. However, not only do classical treatments such as chemotherapies and radiotherapies target tumor cells, but also they cause damage to several healthy cells. For these reasons, the search for new biologically active chemotherapeutic components is of great importance. In this study, we investigated the effect of Tityus serrulatus scorpion venom (TsV) on CC lines. There are very few studies exploring venom of scorpions, and, to our knowledge, no study has been conducted using the venom of the scorpion TsV for treatment of cervical cancer lines. After challenge with TsV, the MTT assay demonstrated cytotoxic effect on HeLa line. Similarly, the cell death process in HeLa analyzed by flow cytometry suggests death via caspase, since the pan-caspase inhibitor z-VAD-fmk significantly reduced the apoptotic response to the treatment. These results suggest that venom of TsV can be a potential source for the isolation of effective antiproliferative and apoptotic molecules in the treatment of CC.